2001
DOI: 10.1523/jneurosci.21-20-08145.2001
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory and Inhibitory Circuitry in the Superficial Gray Layer of the Superior Colliculus

Abstract: Stratum griseum superficiale (SGS) of the superior colliculus receives a dense cholinergic input from the parabigeminal nucleus. In this study, we examined in vitro the modulatory influence of acetylcholine (ACh) on the responses of SGS neurons that project to the visual thalamus in the rat. We used whole-cell patch-clamp recording to measure the responses of these projection neurons to electrical stimulation of their afferents in the stratum opticum (SO) before and during local pressure injections of ACh. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 56 publications
3
50
0
Order By: Relevance
“…In cases that were used for double labeling, injections of WGA conjugated to apo-HRP conjugated to gold particles (GPs) (15-nm particle size, E-Y Laboratories) was injected into the left SC (Lee et al 2001). The survival period after the GP injection was 7-28 days.…”
Section: E T H O D Smentioning
confidence: 99%
“…In cases that were used for double labeling, injections of WGA conjugated to apo-HRP conjugated to gold particles (GPs) (15-nm particle size, E-Y Laboratories) was injected into the left SC (Lee et al 2001). The survival period after the GP injection was 7-28 days.…”
Section: E T H O D Smentioning
confidence: 99%
“…Previous studies suggested that GABA C Rs expressed predominantly in SGS GABAergic neurons have a role in disinhibitory circuitry (Lee et al, 2001;Schmidt et al, 2001). We investigated the effect of muscimol, which activates GABA C Rs and inhibits specifically GABAergic neurons, on the bursts evoked under our experimental condition.…”
Section: Synaptically Released Gaba Activates Gaba B Rs In the Scmentioning
confidence: 99%
“…Its superficial layers [stratum griseum superficiale (SGS) and stratum opticum (SO)] receive visual information from the retina and primary visual cortex, and its deeper layers [stratum griseum intermediale (SGI) and stratum griseum profundum (SGP)] send descending motor commands to the brainstem reticular formation and spinal cord. Previous studies showed that stimulation of the superficial layers induces excitatory synaptic responses in the deeper layers in slice preparations (Lee et al, 1997(Lee et al, , 2001Isa et al, 1998;Helms et al, 2004). In particular, when the slices were treated with GABA A receptor (GABA A R) antagonists such as bicuculline or gabazine, stimulation with single current pulses of the superficial layers elicits bursting responses in deeper layer neurons including crossed tecto-reticular neurons, output neurons projecting to the brainstem gaze center (Saito and Isa, 2003;Sooksawate et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This cholinergic pathway reduces the level of activity of superficial layer cells (Lee et al, 2001) and may provide a spatially selective modulation of visual signals relayed to SGI. Moreover, the adjacent midbrain tegmentum contains GABAergic cells that project to the superior colliculus (Appell and Behan, 1990) and may mediate global inhibition.…”
Section: Evidence For Widespread Inhibition and Excitation Within Sgimentioning
confidence: 99%